Analisis Kebutuhan Torsi Penjatah Pupuk Butiran Tipe Edge-Cell untuk Mesin Pemupuk Jagung - Annisa Nur Ichniarsyah; Wawan Hermawan; Tineke Mandang (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2014)
A study on the design of metering device which could work more optimally was conducted to overcome the high friction between the rotor and its metering tube, and the clogging of fertilizer particle on the conventional rotor type metering device. An edge-cell rotor type metering device was proposed to overcome the problems. Objectives of the study were to analyze the torque requirement of the edge-cell type metering device and to design metering device of corn fertilizer applicator with lower torque requirements and high accuracy. A mathematical model to calculate the torque requirement of the rotor was developed and validated using torque measurement in the experiment. Experiments were conducted using a model of fertilizer applicator equipped with a rotor torque measuring sensor and rotated using an electric motor. The torque measurement results showed that the edge-cell type metering device could reduce the torque requirement up to 68% and 80% when tested using urea and TSP, respectively. By using the edge-cell type rotor, there was no problem of clogging of fertilizer particle on the rotor system. The validation results showed that the mathematical model could predict accurately the torque requirement of the rotor only on the lower volume of fertilizer (25%) in the hopper. However, on the higher volume of fertilizer (50% and 100%) in the hopper, the calculated torques was 2-4 times higher than the actual measuring torques. The amount of the fertilizer in the hopper not significantly affected the torque requirement of the rotor.ABSTRAKPenelitian mengenai desain penjatah pupuk yang dapat berfungsi lebih optimal dilakukan untuk mengatasi besarnya gaya gesek yang terjadi antara rotor penjatah dan ruang penjatah, serta terjadinya kemacetan perputaran rotor penjatah pupuk pada alat pemupuk dalam penelitian sebelumnya. Tujuan penelitian ini adalah menganalisis kebutuhan torsi penjatah pupuk tipe edge-cell. Model pendugaan matematis untuk menghitung kebutuhan torsi telah dibangun dan divalidasi melalui pengujian kebutuhan torsi. Pengukuran dilakukan enggunakan model alat pemupuk jagung yang dilengkapi dengan sensor pengukur torsi. Penjatah tersebut diputar menggunakan motor AC variable speed. Hasil pengukuran torsi menunjukkan bahwa penjatah tipe edge-cell mampu mengurangi kebutuhan torsi penjatahan hingga 68% (pupuk urea) dan 80% (pupuk TSP). Kemacetan yang terjadi akibat ganjalan butiran pupuk yang besar pada ruang penjatah tidak terjadi saat menggunakan penjatah tipe edge-cell. Hasil pengujian validasi model menunjukkan bahwa model matematis mampu menduga kebutuhan torsi dengan akurat hanya pada saat tingkat volume pupuk dalam hopper 25%. Semakin tinggi volume pupuk dalam hopper (50 dan 100%), hasil pendugaan torsi lebih besar sekitar dua hingga empat kali hasil pengukuran torsi. Volume pupuk dalam hopper tidak berpengaruh signifikan terhadap kebutuhan torsi pada rotor.